Growth of Acidithiobacillus Ferrooxidans ATCC 23270 in Thiosulfate Under Oxygen-Limiting Conditions Generates Extracellular Sulfur Globules by Means of a Secreted Tetrathionate Hydrolase - Beard, Simon; Paradela, Alberto; Albar, Juan P.; Jerez, Carlos A. (Frontiers in Microbiology, 2011)
Production of sulfur globules during sulfide or thiosulfate oxidation is a characteristic feature of some sulfur bacteria. Although their generation has been reported in Acidithiobacillus ferrooxidans, its mechanism of formation and deposition, as well as the physiological significance of these globules during sulfur compounds oxidation, are currently unknown. Under oxygen sufficient conditions (OSC), A. ferrooxidans oxidizes thiosulfate to tetrathionate, which accumulates in the culture medium. Tetrathionate is then oxidized by a tetrathionate hydrolase (TTH) generating thiosulfate, elemental sulfur and sulfate as final products. We report here a massive production of extracellular conspicuous sulfur globules in thiosulfate-grown A. ferrooxidans cultures shifted to oxygen-limiting conditions (OLC). Concomitantly with sulfur globule deposition, the extracellular concentration of tetrathionate greatly diminished and sulfite accumulated in the culture supernatant. A. ferrooxidans cellular TTH activity was negligible in OLC incubated cells, indicating that this enzymatic activity was not responsible for tetrathionate disappearance. On the other hand, supernatants from both OSC- and OLC-incubated cells showed extracellular TTH activity, which most likely accounted for tetrathionate consumption in the culture medium. The extracellular TTH activity described here: (i) gives experimental support to the TTH-driven model for hydrophilic sulfur globule generation, (ii) explains the extracellular location of A. ferrooxidans sulfur deposits, and (iii) strongly suggests that the generation of sulfur globules in A. ferrooxidans corresponds to an early step during its adaptation to an anaerobic lifestyle.